Influence of rice field agrochemicals on the ecological status of a tropical stream - Jessen Rasmussen, Jes (2016)
Many tropical countries contain a high density of protected ecosystems, and these may often be bordered by intensive agricultural systems. We investigated the chemical and ecological status of a stream connecting an area with conventional rice production and a downstream protected nature reserve; Mata Redonda. Three sites were sampled: 1) an upstream control, 2) in the rice production area and 3) a downstream site in Mata Redonda. We sampled benthic macroinvertebrates and pesticides in water and sediments along with supporting physical and chemical data. Pesticide concentrations in water exceeded current safety thresholds at sites 2 and 3, especially during the rainy season, and sediment associated pesticide concentrations exceeded current safety thresholds in three of six samples. Importantly, the highest predicted pesticide toxicity in sediments was observed at site 3 in the Mata Redonda confirming that the nature reserve received critical levels of pesticide pollution from upstream sections. The currently used macroinvertebrate index in Costa Rica (BMWP-CR) and an adjusted version of the SPecies At Risk index (SPEAR) were not significantly correlated to any measure of anthropogenic stress, but the Average Score Per Taxon (ASPT) index was significantly correlated with the predicted pesticide toxicity (sumTUD. magna), oxygen concentrations and substrate composition. Our results suggest that pesticide pollution was likely involved in the impairment of the ecological status of the sampling sites, including site 3 in Mata Redonda. Based on our results, we give guidance to biomonitoring in Costa Rica and call for increased focus on pesticide transport from agricultural regions to protected areas.